AIAA Modeling and Simulation Technologies Conference 2015
DOI: 10.2514/6.2015-1594
|View full text |Cite
|
Sign up to set email alerts
|

Full Flight-Envelope Simulation and Piloted Fidelity Assessment of a Business Jet Using a Model Stitching Architecture

Abstract: This paper presents the development and piloted assessment of a full flight-envelope simulation model of a light business jet using a model stitching architecture. Individual state-space models and trim data for discrete flight conditions were combined to produce a continuous simulation model, which was integrated into a fixed-base simulation facility. Back-to-back flight/simulation piloted evaluations of a similar light business jet in flight and the stitched model in simulation were performed to assess the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A more complete description of the bare-airframe stitched model used in this study is provided by Tobias et al 11 Tobias also presents the results of a simulation fidelity test using back-to-back flight and simulator testing, which show excellent agreement in pilot control strategy and workload between the stitched model and actual aircraft. …”
Section: Bare-airframementioning
confidence: 94%
See 1 more Smart Citation
“…A more complete description of the bare-airframe stitched model used in this study is provided by Tobias et al 11 Tobias also presents the results of a simulation fidelity test using back-to-back flight and simulator testing, which show excellent agreement in pilot control strategy and workload between the stitched model and actual aircraft. …”
Section: Bare-airframementioning
confidence: 94%
“…10 For the piloted simulation evaluation, a continuous, full-envelope model is needed, in lieu of the individual point models. This was accomplished using the model stitching technique, 8,11 which refers to the process of combining a collection of linear state-space models at various fight conditions with trim data into a full-envelope simulation model. As shown in Figure 3, model stitching is accomplished by implementing lookup tables of the aircraft state trim values, control input trim values, and stability and control derivatives with respect to total instantaneous x-body axis relative velocity, U , based on the point models and trim data extracted from the AAA nonlinear simulation model.…”
Section: Bare-airframementioning
confidence: 99%
“…Trim data were included for flap settings of 15 and 35 deg, while the stability and control derivatives remain at the nominal (flaps-up) configuration (see Section 3.8). This approach ensures that flaps-down trim is correct, which is important for piloted simulation [17], and allows for efficient flight testing. Cost permitting, it may be advantageous, however, to directly identify the dynamics of a single flaps-down approach configuration using system identification flight testing.…”
Section: Aircraft Configurationsmentioning
confidence: 99%
“…This technique provided continuous look-up of trim and derivatives with deflection of flaps and changes in airspeed for a high-fidelity simulated approach to landing. Pilot reaction indicated that trim behavior, and the corresponding migration of the controls, however, were the most important effects upon deployment of flaps [17].…”
Section: Simulation Of Alternate Configurations -Flap Settingmentioning
confidence: 99%
See 1 more Smart Citation